An Assessment of the Dimensionality and Factorial Structure of the Revised Paranormal Belief Scale - Drinkwater, Kenneth; Denovan, Andrew; Dagnall, Neil; Parker, Andrew (Frontiers in Psychology, 2017)
Since its introduction, the Revised Paranormal Belief Scale (RPBS) has developed into a principal measure of belief in the paranormal. Accordingly, the RPBS regularly appears within parapsychological research. Despite common usage, academic debates continue to focus on the factorial structure of the RPBS and its psychometric integrity. Using an aggregated heterogeneous sample (N = 3764), the present study tested the fit of ten factorial models encompassing variants of the most commonly proposed solutions (seven, five, two and one-factor) plus new bifactor alternatives. A comparison of competing models revealed a seven-factor bifactor solution possessed superior data-model fit (CFI = .945, TLI = .933, IFI = .945, SRMR = .046, RMSEA = .058), containing strong factor loadings for a general factor and weaker, albeit acceptable, factor loadings for seven subfactors. A comparison of competing models found superior fit for a seven-factor bifactor solution. This indicated that belief in the paranormal, as measured by the RPBS, is best characterised as a single overarching construct, comprising several related, but conceptually independent subfactors. Furthermore, women reported significantly higher paranormal belief scores than men, and tests of invariance indicated that mean differences in gender are unlikely to reflect measurement bias. Results indicate that despite concerns about the content and psychometric integrity of the RPBS the measure functions well at both a global and seven-factor level. Indeed, the original seven-factors contaminate alternative solutions.